FACEBOOK OVERSIGHT BOARD’S DECISION ON THE INDEFINITE SUSPENSION OF DONALD TRUMP’S ACCOUNT - Vukčević, Ivana (Pravni zapisi, 2021)
On May 5, 2021 Facebook Oversight Board, a global body created by the company to act as an independent appeals mechanism for Facebook’s content moderation, issued its highly awaited decision concerning the “indefinite suspension” of former US President Donald Trump’s account. The suspension was originally imposed by Facebook between January 6 and 7, 2021 for Trump’s posts related to the attacks on Capitol Hill in Washington, DC. This case note shows the Oversight Board’s almost exclusive reliance on international human rights standards in deciding the case. It sees it as a positive development. Additionally, the author argues that the decision also highlights Facebook’s struggle and potential lack of willingness to develop a unified approach to its treatment of political leaders and the company’s reluctance to grapple with the way its business model has potentially contributed to violent events, including the attacks on the Capitol Hill on January 6, 2021.
Keywords: Facebook; Oversight Board; Donald Trump; freedom of expression; social media; content moderation; indefinite suspension; political leaders; high-profile accounts; international human rights law